Study On Human Resources Readiness Of Sea Cross-Border Post (PLBN) In Riau Islands Province - Elmi, Farida; Yusoff, Yusliza M.; Setyadi, Antonius; Sutarman, Novia Nila (Inisiatif Masyarakat Jurnal Indonesia (IMAJI), 2024)
This study aims to examine the readiness of human resources and the process of placing employees at the Sea Cross-border Post (PLBN) in Riau Archipelago Province. This research used a qualitative method with a descriptive approach. Data was collected through in-depth interviews with eight key informants, observations and documentation. Instrument testing was carried out using triangulation and Nvivo12. This study provides an overview of the readiness of human resources and the process of placing employees at PLBN. The findings of this study can become a basis for the government in planning and adopting policies related to human resource management in other PLBNs. The PLBN is also considered to generate high-quality human resources, with the hope that it will contribute significantly to the economic development of the Riau Archipelago Province in the future.